THE PROBLEMS OF PROVIDING INFECTIOUS DISEASE SAFETY FOR ORGAN AND TISSUE DONATION BY SCREENING BLOOD-BORNE VIRAL INFECTIONS - M. Sh. Khubutiya; S. A. Solonin; M. A. Godkov (Вестник трансплантологии и искусственных органов)
It provided data on the prevalence, clinical signifi cance and methods of laboratory diagnostics for occult forms of blood-borne viral infections (BBVIs). It considered causes of such forms of infection and their signifi cance for clinical transplantation. We analyzed the existing algorithm of laboratory screening of a potential organ donor for BBVIs in Russia. It is shown that the current screening algorithm doesn’t allow detecting hidden forms of BBVIs.